Introducing Teacherpreneurship in the Scope of Theological Seminary Lecturers - Latuputty, Sientje; Fonataba, Henny Verra; Jura, Demsy (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
The article titled "Introducing Teacherpreneurship in the Context of Theological Seminary Lecturers" is a conceptual exploration aimed at grounding the concept of teacherpreneurship among lecturers at theological seminary. Teacherpreneurship, understood as the implementation of entrepreneurial spirit within a lecturer, requires the ability to engage in entrepreneurship as an effort to firmly develop all existing potential and aimed at maximizing oneself as a professional theology lecturer with significant results The goal of this research is to strive for an accurate understanding of the entrepreneurial spirit within theological seminary lecturers so that through their teaching ministry, they can produce meaningful outcomes. A qualitative approach with literature study is employed in this research to obtain relevant library information related to the discussed theme.